Employment propensity: The roles of mental and physical health - Gail Pacheco; Don J. Webber (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2011)
This paper presents an investigation into the impacts of mental and physical health on the propensity to be employed. Health status is parameterised using three physical and three mental health indicators. After controlling for various socioeconomic factors, the application of limited dependent variable regression techniques generates results which indicate that activity-limiting physical health and accomplishment-limiting mental health issues significantly affect the propensity to be employed. Further investigations reveal gender and ethnicity divides and that health is exogenous to employment status.
Keywords: I1; J29; J16; 330; Mental health; Physical health; Employment status; Ethnicity; Gender